In vitro comparison of the force degradation of orthodontic intraoral elastics from different compositions - Vieira, Camila Ivini Viana [UNESP] (2013)
The synthetic intermaxillary elastic emerged as an alternative for clinical use in patients with latex sensitivity. However, there are disagreements about this elastic protocol use according to the force degradation. The aim of this study was to evaluate, in vitro, the forces generated by latex and synthetic elastics over time. Material and methods: Sample size of 840 elastics were used (420 latex and 420 synthetic), delivering medium strength (Dental Morelli®) with internal diameter of 1/8", 3/16", 1/4" and 5/16". The elastics were randomly divided into 7 groups according to the time of the force measuring and immersed into distilled water at 37°C. To measure the force in each group, the elastics were stretched in six progressive increases of 100% of its internal diameter with the aid of a testing machine Emic and measured up to 72 hours. Data were analyzed with SPSS 16.0, using one-way analysis of variance (ANOVA). Results: Immediate force level of synthetic elastics was statistically higher than latex elastics in all strains, for the same size. However, the latex elastics mean forceslightly decreased over time, while the synthetic elastics presented an abrupt decrease. Conclusion: In view of these findings, Sudanese homemade alcoholic beverages cause oral epithelial atypical changes, which lead to oral precancerous and cancerous lesions. OEFC is a useful procedure for detection and assessment of oral ET.